An Ancestral Role for CONSTITUTIVE TRIPLE RESPONSE1 Proteins in Both Ethylene and Abscisic Acid Signaling. Issue 1 (4th August 2015) - Yasumura, Yuki; Pierik, Ronald; Kelly, Steven; Sakuta, Masaaki; Voesenek, Laurentius A.C.J.; Harberd, Nicholas P.
Abstract : A Physcomitrella patens protein regulates both ethylene and abscisic acid signaling, and this dual function was subsequently lost during evolution. Abstract: Land plants have evolved adaptive regulatory mechanisms enabling the survival of environmental stresses associated with terrestrial life. Here, we focus on the evolution of the regulatory CONSTITUTIVE TRIPLE RESPONSE1 (CTR1) component of the ethylene signaling pathway that modulates stress-related changes in plant growth and development. First, we compare CTR1-like proteins from a bryophyte, Physcomitrella patens (representative of early divergent land plants), with those of more recently diverged lycophyte and angiosperm species (including Arabidopsis [ Arabidopsis thaliana ]) and identify a monophyletic CTR1 family. The fully sequenced P. patens genome encodes only a single member of this family (PpCTR1L). Next, we compare the functions of PpCTR1L with that of related angiosperm proteins. We show that, like angiosperm CTR1 proteins (e.g. AtCTR1 of Arabidopsis), PpCTR1L modulates downstream ethylene signaling via direct interaction with ethylene receptors. These functions, therefore, likely predate the divergence of the bryophytes from the land-plant lineage. However, we also show that PpCTR1L unexpectedly has dual functions and additionally modulates abscisic acid (ABA ) signaling. In contrast, while AtCTR1 lacks detectable ABA signaling functions, Arabidopsis has during evolution acquired another homolog that is functionally distinct from AtCTR1. In conclusion, the roles of CTR1-related proteins appear to have functionally diversified during land-plant evolution, and angiosperm CTR1-related proteins appear to have lost an ancestral ABA signaling function. Our study provides new insights into how molecular events such as gene duplication and functional differentiation may have contributed to the adaptive evolution of regulatory mechanisms in plants.